Experimental and theoretical analysis of strain hardening behavior of friction-stir-welded Al-4.2Zn-3.1Mg aluminium alloy - Verma S.; Sharma S.; Misra J.P.; Singh R.A.; Jayalakshmi S. (My University, 2025)
The strain hardening behavior of friction stir welded AA7039 (Al-4.2Zn-3.1 Mg) alloy was explored in terms of dislocation density, crystallite size, hardening capacity, hardening exponent, and strain hardening rate. Strain hardening behavior was analyzed for base metal and friction stir welded specimens. Four different models were used to calculate the dislocation density viz., Scherrer model, uniform strain model (USM), uniform stress distribution model (USDM), and uniform strain energy distribution model (USDEM). Maximum dislocation density was obtained in base metal for all models (maximum for USM, 3.9 (Formula presented.) with a minimum crystallite size of 15.81 nm. The low dislocation density in FSW samples is due to the higher heat input in the FSW process. Strain hardening stages were shown by Kocks–Mecking type plots. Lower strain hardening capacity was obtained for BM, i.e. 0.427 as compared to FSW samples, due to the higher dislocation density of BM. It was determined that there is an inverse relationship between the strain hardening capacity and the strain hardening exponent. Strain hardening rate was higher for BM than FSW specimens, and similar results were obtained from mathematical relations that indicate the adequacy of the results. The ultimate tensile strength was 2.5% higher than the BM at a rotational speed of 1325 rpm, 35 mm/min of welding speed and 1.65° tilt angle. The maximum strength friction stir-welded specimen showed a more ductile fracture surface than the BM because the grain boundary phase disappeared or broke up in the thermomechanical affected zone. © 2024 Informa UK Limited, trading as Taylor & Francis Group.